Effect of formulated entomopathogenic fungi on red gum lerp psyllid Glycaspis brimblecombei - Dal Pogett, Mário Henrique Ferreira do Amaral [UNESP]; Wilcken, Carlos Frederico [UNESP]; Christovam, Rafael da Silva [UNESP]; Prado, Evandro Pereira [UNESP]; Gimenes, Marcelo Júnior [UNESP] (Science Alert, 2011)
The objective of this study was to evaluate the potential use of formulated entomopathogenic fungi to be used as alternative method for the management of red gum lerp psyllid Glycaspis brimblecombei. The bioassay was carried out in laboratory using three species of fungi and six commercial brands: Beauveria bassiana (Boveril WP, Toyobo and Mycotrol O); Metarhizium anisopliae (Metarril WP and Toyobo); Lecanicillium longisporum (Vertirril WP). Five concentrations of each product were sprayed over the nymph kept on eucalyptus leaves. The results of mortality due to concentrations and time were used to calculate the LC50 and LT50. All tested products were pathogenic to the red gum lerp psyllid and the products Metarril WP, Vertirril WP and Mycotrol O were more virulent. For these products the average death rate was above 90% in the highest concentration while LT50 varied between 1.4 and 2.3 days. The results indicate that the microbial control of red gum lerp psyllid with entomopathogenic fungi is viable and has potential to be used as an alternative control to this pest in eucalyptus forests.
Keywords: Mycoinsecticides; Beauveria bassiana; Metarhizium anisopliae; Lecanicillium longisporum; Eucalyptus